Adaptação e validação de conteúdo dos instrumentos de medida do controle clínico que compõem o sistema eletrônico para a avaliação, suporte e monitoramento da asma para adultos (e-ASMA) - Barbosa, Joubert Vitor de Souto (2023)
Introduction: In Brazil, asthma control assessment has been performed using measurement tools originally developed in English, translated, and validated for Portuguese. These instruments play a crucial role in early detection of asthma control levels, enabling self-management of the disease and delaying potential symptoms. Objective: The aim of this study was to adapt and assess the content validity of two asthma control measurement instruments, the Asthma Support and Monitoring Assessment Questionnaire (qASMA) and the Asthma Support and Monitoring Assessment Diary (dASMA), for the adult population. These instruments are part of the electronic system for Asthma Support and Monitoring (e-ASMA). Methods: This study employed a methodological exploratory design to evaluate measurement properties with adults aged 18 years and above, diagnosed with asthma at any level of control according to the Global Initiative for Asthma (GINA). The study was approved by the Ethics and Research Committee of UFRN (CAAE: 35771920.2.0000.5537, and APPROVAL: 4.895.038) and is linked to the project "Development and Validation of an Electronic System for Asthma Assessment, Support, and Monitoring (e-ASMA)," approved under CNPq/MCTI/FNDCT Call No. 18/2021 – UNIVERSAL. This project followed the international recommendations of the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) and comprised two phases: (1) conceptual and semantic adaptation of qASMA and dASMA for the adult population, resulting in preliminary versions of the instruments; (2) Content validation of qASMA and dASMA. The adaptation of the adult versions of qASMA and dASMA, along with their content validation, involved initial item adaptation through researcher consensus, followed by judgment by a committee of judges, and a pre-test conducted through in-depth interviews with adults with asthma. Results: The items comprising qASMA and dASMA were initially adapted by three researchers in the study. After the initial adaptation, the instruments were evaluated by a committee of 10 judges following COSMIN criteria for assessing the relevance and comprehensiveness of the questionnaire and diary items. Initially, five items in qASMA and one item in dASMA showed Fleiss' kappa values below the acceptable threshold (0.70). These items were adjusted, resubmitted for the judges' evaluation, and approved. Subsequently, in-depth interviews were conducted with 15 representatives of the target population to assess the comprehension, relevance, and comprehensiveness of the measurement instruments' items. Overall, the instrument items were considered clear, relevant, and understandable, with minor adjustments proposed for the final wording of some items. Conclusion: The adaptation stages of the instruments supported their content validation, indicating that the items in qASMA and dASMA are relevant, understandable, and comprehensive for the target population. The versions of qASMA and dASMA demonstrate adequate content validity for Brazilian adults.